Enhanced water vapor barrier property of poly(chloro-p-xylylene) film by formation of dense surface cross-linking layer via hyperthermal hydrogen treatment1. Issue 69 (29th July 2015) - Shao, Hong; Hu, Xin; Xu, Keqin; Tang, Changyu; Zhou, Yuanlin; Shuai, Maobing; Mei, Jun; Zhu, Yan; Lau, Woon-ming
<x xml:space="preserve">Abstract</x> C–H bonds on PPXC film were preferentially cleaved by hydrogen bombardment and then formed a cross-linking moisture barrier layer.